El Excentrico, 1965-03-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
March 5, 1965 [5 de marzo de 1965]. Ano 15, No 10. Cover has photograph of a cartoon caricature of an angry woman with headline, "Adorable Mother- In Law."